The Ratio and Point Analysis of the Functionality of Process Management Systems - Stabryła, Adam (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper presents the concept of functionality analysis as a universal research method applied in organisational and technical as well as economic and social systems. The methodology of functionality analysis is based on a functional approach, which indicates that systems are analysed from the perspective of the functions they perform. A functional approach translates to various methodologies, constituting a link between diagnosing research and designing. The paper presents functionality analysis as a diagnostic method focused on ratio and point assessment.